Computational intelligence and intelligent systems : 7th International Symposium, ISICA 2015, Guangzhou, China, November 21-22, 2015, Revised selected papers /: 7th International Symposium, ISICA 2015, Guangzhou, China, November 21-22, 2015, Revised selected papers. (2016) - Unknown
No abstract available